Inequality : a reassessment of the effect of a family and schooling in America - Jencks , Christopher...[et al.] (New York, 1972)
Details the findings of a three-year study undertaken at the Center for Educational Policy Research on inequality in schooling in America and its relation to economic success.
Keywords: Inequality